Gut Microbiome Succession in Chinese Mitten Crab Eriocheir sinensis During Seawater–Freshwater Migration - Shao, Chenxi; Zhao, Wenqian; Li, Nannan; Li, Yinkang; Zhang, Huiming; Li, Jingjing; Xu, Zhiqiang; Wang, Jianjun; Gao, Tianheng (Frontiers in Microbiology, 2022)
Biological migration is usually associated with disturbances and environmental changes that are key drivers in determining the diversity, community compositions and function of gut microbiome. However, little is known about how gut microbiome is affected by disturbance such as salinity changes during migration from seawater to freshwater. Here, we tracked the gut microbiome succession of Chinese mitten crabs (Eriocheir Sinensis) during their migrations from seawater to freshwater and afterwards using 16S rDNA sequencing for 127 days, and explored the temporal patterns in microbial diversity and the underlying environmental factors. The species richness of gut microbiome showed a hump-shaped trend over time during seawater-freshwater migration. The community dissimilarities of gut microbiome increased significantly with day change. The turnover rate of gut microbiome community was higher during seawater-freshwater transition than that in later freshwater conditions. Salinity was the major factor leading to the alpha diversity and community dissimilarity of gut microbiome during seawater-freshwater transition, while the host selection showed dominant effects during freshwater stage. The transitivity, connectivity and average clustering coefficient of gut microbial co-occurrence networks showed decreased trends, while modularity increased during seawater-freshwater migration. For metabolic pathways, “Amino Acid Metabolism” and “Lipid Metabolism” were higher during seawater-freshwater transition than in freshwater. This study advances our mechanistic understanding of the assembly and succession of gut microbiota, which provides new insights into the gut ecology of other aquatic animals.